Rekonstruksjon av isavsmeltingsforløpet i Gråsteindal-området, indre Sunnmøre - Nygård, Line (The University of Bergen, 2017)
The North-Western part of Norway became ice free during the Late Weichselian glaciation and the ice margin is mapped across several fjord districts. Distinct moraine systems in the high mountains indicate an extensive local glaciation during the Younger Dryas. The purpose of this thesis is to reconstruct the deglaciation history of Gråsteindalen valley and the eastern side valley based on Quaternary geological and geomorphological mapping, cosmogenic nuclide ages and reconstruction of ELA (equilibrium-line altitude). Exposure ages of rock surface samples from Hesjedalshaugen and Grandehaugen west of Gråsteindalen valley indicate that the deglaciation of the main and side valley started before 17,7 ka in the Late Weichselian. At the southern end of Gråsteindalen valley a prominent lateral moraine has been studied by several people and it has been claimed to be of Younger Dryas age (Eikenæs 1991; Aarseth et al. 1997). An additional exposure age of 11,3 ± 1,48 ka indicates that the lateral moraine was deposited by the ice sheet during the advance in Younger Dryas. Terminal moraines in Gråsteindalen valley and the side valley are believed to be of the same age as the lateral moraine in the valley side adjacent to Geirangerfjorden, and indicate that the high mountains had local glaciers, leaving an ice-free area between the local glaciers and the ice sheet. Observations of several marginal moraines indicate that there were cirque and valley glacier advancing during the Younger Dryas. The result from the Quaternary geological and geomorphological mapping reveals terminal moraines from several glacier advances, where some of them are believed to be of Younger Dryas age (12,8-11,7 ka) and another advance associated with the Erdalen Event (10,1-9,7 ka). The most recent glacier advances are thought to have happened during the Little Ice Age (ca. 1300-1920), resulting in terminal moraines at the proximal side of the threshold of the Trollkupa cirque. It is believed that the glaciers were isolated cirque glaciers during the ...